Pengembangan Pariwisata Berbasis Tri Hita Karana (Studi Pengembangan Pariwisata Berkelanjutan di Bali) - Ketut Dibya (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2018)
Bali is well known by the world community as a place that has many attractions. This tourist attraction encourages domestic and foreign tourists come to Bali. In addition to having a positive impact on local revenue or improving the welfare of surrounding communities, on the other hand there are problems related to the development of unplanned tourism. The development of unplanned tourism sector has caused negative impacts, traffic congestion, environmental degradation and diversion of agriculture farming functions which is used as the development of tourism facilities. To overcome the negative impact of tourism development, the development of tourism in Bali should be devoted to the development of sustainable tourism. One of the local wisdom in Bali that can be used as a foothold in the effort to realize the development of tourism is Tri Hita Karana. Tri Hita Karana is a concept built on the principle of harmony of life which consists of three elements that are interconnected with each other. The three elements are,parahyangan, pawongan, and palemahan. Parahyangan in harmony of relationship betweenhuman with God, pawongan goods harmony with human relationship, and palemahan tradeharmony with environment and nature. Implementation of of the concept of parahyangan can bedone by building places of worship around the tourist area, conducting prayer activities.Implementation of the concept of pawongan can be done by greeting each other with “OmSwastyastu” to all people encountered and maintain intimacy among religious people.Implementation of the concept of palemahan can be done by not storing garbage carelessly,keeping the environment free of air pollution, greening and tree planting.Keywords: Culture, Tourism, Sustainable Tourism